Pemasangan Papan Wicara Tentang Lama Waktu Urai Sampah dan Poster Menjaga Kebersihan Lingkungan di Desa Tonasa Kecamatan Sanrobone Kabupaten Takalar - Mahfudah, Ulfah; Mahmudah Dulla, Arif Atul (Patria Artha Journal of Community (PKM), 2025)
This community service activity aims to increase public awareness and concern for waste management and environmental cleanliness. The intervention was carried out through the installation of information boards containing information about the decomposition time of various types of waste and the installation of posters about the importance of maintaining environmental cleanliness. This activity was carried out in six hamlets, Tonasa I, Tonasa II, Bontoa, Lebbae, Pa'rasangan Beru I, and Pa'rasangan Beru II. The community responded positively to these physical interventions. The information boards were considered to provide new knowledge, especially regarding the fact that plastic waste takes hundreds of years to decompose. The posters were also considered attractive and easy to understand, even serving as a learning tool for children. Overall, this activity received high appreciation from the community as it was deemed beneficial and increased awareness of the importance of maintaining environmental cleanliness.